2019
DOI: 10.1142/s0219581x19400301
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Diagnostics of Free Charge Carriers in Silicon Nanowires

Abstract: Free charge carrier concentration in arrays of silicon nanowires (SiNWs) with cross-sectional size of the order of 100[Formula: see text]nm was quantitatively studied by means of the infrared spectroscopy in an attenuated total reflection mode. SiNWs were formed on lightly-doped [Formula: see text]-type crystalline silicon substrates by metal-assisted chemical etching followed by additional doping through thermoactivated diffusion of boron at 900–1000∘C. The latter process was found to increase the concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Recently, it has been shown that MACE‐fabricated SiNWs can be additionally doped using standard microelectronic thermo‐diffusion approach. [ 7–11 ] Optical methods such as Fourier‐transform infrared (FTIR) spectroscopy in attenuated total reflection (ATR) mode [ 7–9,11 ] and Raman spectroscopy [ 10,11 ] have been employed to probe the concentration of FCC in SiNW arrays. While the FTIR‐ATR diagnostics is highly sensitive to FCC of both types (electrons and holes), it should be applied under the conditions of an effective medium approximation, which requires precise knowledge of the porosity value of SiNW array.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that MACE‐fabricated SiNWs can be additionally doped using standard microelectronic thermo‐diffusion approach. [ 7–11 ] Optical methods such as Fourier‐transform infrared (FTIR) spectroscopy in attenuated total reflection (ATR) mode [ 7–9,11 ] and Raman spectroscopy [ 10,11 ] have been employed to probe the concentration of FCC in SiNW arrays. While the FTIR‐ATR diagnostics is highly sensitive to FCC of both types (electrons and holes), it should be applied under the conditions of an effective medium approximation, which requires precise knowledge of the porosity value of SiNW array.…”
Section: Introductionmentioning
confidence: 99%
“…While the FTIR‐ATR diagnostics is highly sensitive to FCC of both types (electrons and holes), it should be applied under the conditions of an effective medium approximation, which requires precise knowledge of the porosity value of SiNW array. [ 7–9 ] In contrast to the FTIR‐ATR analysis, the Raman spectroscopy in a micro‐Raman mode allows us to probe the FCC density in the depth of SiNW arrays. [ 10 ] The main physical effect responsible for the Raman spectroscopy of FCC in SiNWs is related to the Fano resonance, which is well known for c‐Si.…”
Section: Introductionmentioning
confidence: 99%